Symbian for software leaders : principles of successful Smartphone development projects - Wood, David, 1957- (John Wiley & Sons, 2006)
"Smartphones are mobile rich portals into the ever-expanding, ever more important digital universe. As with any revolutionary new technology, Symbian OS poses challenges to software developers at a management as well as a technical level. This is the first book to address the wider set of skills and thought processes necessary to successfully complete smartphone development projects."--Jacket